Legal Protection Against Status Determination of Suspects for Unpleasant Crimes After the Decision of the Constitutional Court Number 1/PUU-XI/2013 - Xavier Nugraha; Peter Jeremiah Setiawan; Citi Rahmati Serfiyani (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2021)
Article 335 paragraph (1) of the Criminal Code and Article 21 paragraph (4) of the Criminal Procedure Code are deemed to be contradicting Article 28D of the 1945 Constitution. Through the Decision of the Constitutional Court Number 1 / PUU-XI / 2013 excluding the phrase "unpleasant actions" because they are considered to cause multiple interpretations and put forward subjectivity. This article is exposed to arbitrary actions by the authorities to criminalize someone. In fact, after the Constitutional Court Decision Number 1 / PUU-XI / 2013, there are still pre-trial cases of determining suspects based on unpleasant acts. The formulation of Article 335 Paragraph (1) of the Criminal Code, which is used after the decision, requires the fulfillment of 2 (two) elements, namely "using violence" or "threat of violence." Thus, in every indictment that wrote the phrase "unpleasant act" was considered a legal reason. Determination of a suspect because this is considered a formal defect